Spectrophotometric determination of ofloxacin in pharmaceuticals and human urine - Vinay, Kanakapura Basavaiah; Revanasiddappa, Hosakere Doddarevanna; Mysore, Divya Ranganath; Rajendraprasad, Nagaraju (Eclética Química, 2009)
Three simple and sensitive spectrophotometric methods are described for the determination of ofloxacin (OFX) in pharmaceuticals and in spiked human urine. First and second methods are based on the measurement of absorbance of OFX in 0.1 M HCl at 293 nm (method A) and 0.1 M NaOH at 287 nm, respectively. The third method is based on the measurement of 2:1 complex formed between OFX and iron(III) in H2SO4 medium, the complex peaking at 420 nm (method C). The optimum conditions for all the three methods are optimized. Beer’s law is obeyed over the ranges 0.63-12.5 using method A and method B, and 10-120 μg mL-1 using method C. The apparent molar absorptivity values are calculated to be 3.5 × 104, 2.76 × 104 and 2.51 × 103 L mol-1cm-1 for method A, method B and method C, respectively. The Sandell sensitivity, limit of detection (LOD) and limit quantification (LOQ) values are also reported. All the methods were validated in accordance with current ICH guidelines. The developed methods were employed with high degree of precision and accuracy for the estimation of total drug content in commercial tablet formulations of DOX.